EP598 Preliminary results of immunohistochemical tumor markers evaluation in endometrial cancer patients. (1st November 2019) - Fais, M; Corvetto, E; Russo, M; Candotti, G; Fanni, D; Faa, G; Locati, V; Proto, A; Mais, V; Peiretti, M
Abstract : Introduction/Background: Endometrial cancer is one the most common female cancers, a better stratification into high- or low-risk is mandatory to identified patients who might benefit of a tailored adjuvant therapy. Recent studies have demonstrated that a new biomarkers panel, assessed immunohistochemically, could be helpful in a better prognosis prediction and thus in patients selection. Methodology: This is a retrospective analysis of the following Immunohistochemical markers: L1 Cell Adhesion Molecule (L1CAM), p53, β-catenin, Ki67, Estrogen receptor (ER) and Progesterone receptor (PR) in patients with diagnosis of endometrial cancer. Results: We analyzed twenty-one patients with a median age of 58 years (range, 34–88 years). Final histology was endometrioid in 14 (66, 6%) cases, clear cell in 1 (4, 8%) case, serous in 5 (23, 8%) cases, mixed in 1 (4, 8%) case. Seven (33%) patients were L1CAM positive (cut off value 10%). L1CAM expression was associated with advanced age (74 years vs 67 years), non-endometrioid morphology and loss of ER and PR expression. An important association was found with p53-mutant tumors often showing diffuse L1CAM expression, mostly in the non-endometrioid subtype. Out of a total of 14 endometrioid endometrial cancer, only one was found to be p53 mutant positive and 13 p53 wild-type (wt) positive. All non-endometrioid EC expressed p53 wt and L1CAM markers and 4/5 (80%) shows a L1CAM positivity >75%. None association was found between L1CAM and Ki67 expression and depth of myometrial invasion, histologic grade, lymph vascular space invasion and metastatic node. Endometrioid and non-endometrioid subtype demonstrated diffuse β-catenin staining >50%. Conclusion: In agreement with the literature, these data confirmed that in high risk endometrial cancer patients L1CAM and p53 expression is more frequent. A high association was found between L1CAM expression and mutant p53 expression in the non-endometrioid subtype endometrial cancer. Disclosure: Nothing to disclose.